1994
DOI: 10.1007/bf01405501
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous malformations of the brain stem

Abstract: A retrospective analysis of 139 patients with brain stem cavernous malformations is presented. The material consists of 41 cases from Bern and Phoenix and 98 further well-documented cases from the literature. Sixty-eight patients were male, 70 were female. The average age was 31.8 + 11.8 years. Sixty-two percent of the cavernous malformations were in the pons, 14% were in the mesencephalon, 12% were in the pontomesencephalic and in the pontomedullary junction, and 5% were in the medulla. Eighty-eight percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
199
1
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(227 citation statements)
references
References 38 publications
6
199
1
12
Order By: Relevance
“…20 The percentage of improved or unchanged functional outcomes was retrospectively reported in relatively small cohorts and ranged from 46.7% to 95.7%. 10,16,23 This study demonstrated that an initial small lesion size, no prospective hemorrhage, and younger age contributed to promote complete recovery. These findings were interpreted as implying that a significant space-occupying effect, cumulative impairment caused by repeated hemorrhages, and advanced age with decreasing potential of rehabilitation or functional compensation would delay or even inhibit functional improvement.…”
Section: Functional Outcomesmentioning
confidence: 55%
“…20 The percentage of improved or unchanged functional outcomes was retrospectively reported in relatively small cohorts and ranged from 46.7% to 95.7%. 10,16,23 This study demonstrated that an initial small lesion size, no prospective hemorrhage, and younger age contributed to promote complete recovery. These findings were interpreted as implying that a significant space-occupying effect, cumulative impairment caused by repeated hemorrhages, and advanced age with decreasing potential of rehabilitation or functional compensation would delay or even inhibit functional improvement.…”
Section: Functional Outcomesmentioning
confidence: 55%
“…10,11,14,19,22,30,34,37,38,42,47,51 Among these studies, Tarnaris et al 47 reported fairly poor outcomes, with 53.3% of patients exhibiting worsening conditions, and cited a neurological deterioration of 10% per patient year. An extremely malignant prognosis was reported with a mortality rate of 20%.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…In 2002, Nagib and O'Fallon [14] summarized nine cases including their two personal cases, and in 2006, Bakir et al [3] reported another pediatric patient with ImCA: Although the number of reported pediatric cases with ImCA is small, we can outline some differences from that of the While ImCA in the adult occur more frequently in women than in men [12,17], with a female/male ratio of approximately 2:1, seven of ten cases of symptomatic ImCA reported in children were male, thus accounting for a male/ female ratio of 2:1. The hypothesis of a hormonal effect leading to a greater risk of bleeding in female adults does not seem to be verified in children, but the mean age at bleeding is 13.2 years (range [8][9][10][11][12][13][14][15][16][17] and can also suggest the hormonal influence of puberty.…”
Section: Special Features Of Imca In Childrenmentioning
confidence: 99%
“…Differences between intracerebral and intraspinal CA A higher risk of bleeding has been identified for ImCA: The actuarial risk of bleeding of cerebral sustentorial lesions is 0.2-0.7% per year [5,13,16] against 1.6% per year in ImCA [11,14] and 2.7% for brainstem CAs [10]. Moreover, the potential for a devastating hemorrhage with significant morbidity is higher for ImCA than for their cerebral counterpart because of the exiguous parenchymatous space where these lesions are located.…”
Section: Special Features Of Imca In Childrenmentioning
confidence: 99%